2003
DOI: 10.1007/bf02700027
|View full text |Cite
|
Sign up to set email alerts
|

Safety, tolerability, and tumor response of IL4-Pseudomonas exotoxin (NBI-3001) in patients with recurrent malignant glioma

Abstract: NBI-3001 appears to have an acceptable safety and toxicity profile when administered intratumorally in patients with recurrent malignant glioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(83 citation statements)
references
References 16 publications
2
80
0
1
Order By: Relevance
“…Eotaxin could regulate eosinophil trafficking into the airways along with other chemotactic factors, such as IL-4 which is a pleiotropic cytokine that elicits a wide spectrum of physiological and pathogenic events including cell proliferation, differentiation, apoptosis and inflammation [26][27][28]. The enhanced level of IL-4 in the asthma subgroup was attenuated with the addition of γT, with almost the same function as dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…Eotaxin could regulate eosinophil trafficking into the airways along with other chemotactic factors, such as IL-4 which is a pleiotropic cytokine that elicits a wide spectrum of physiological and pathogenic events including cell proliferation, differentiation, apoptosis and inflammation [26][27][28]. The enhanced level of IL-4 in the asthma subgroup was attenuated with the addition of γT, with almost the same function as dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal choice among the treatments may depend on the overall time of the infusion protocol. For example, clinical trials of CED of therapeutic proteins often involve infusion protocols that last several days [53]; in some cases multiple infusions are separated by more than a week [13]. For these longer protocols, enzymatic degradation of the ECM may be a preferable strategy to enhance particle distribution, because the regeneration of hyaluronan takes up to 12 days [49].…”
Section: Discussionmentioning
confidence: 99%
“…The safety and toxicity of IL-4(38-37)-PE-38KDEL was also examined in a multicenter, doseescalation phase I/II trial with intratumoral administration in 31 patients with recurrent malignant glioma, and it was suggested that compared to historical control there was an increase in overall median survival. 53 Further development of this agent is planned.…”
Section: Il-4mentioning
confidence: 99%